Sistem Monitoring dan Kontrol Penjernih Greywater Bertenaga Photovoltaic Berbasis Internet of Things (IoT) - Hanifah Nur Kumala Ningrum; Raden Jasa Kusumo Haryo; Ryan Wicaksono; Yudhi Rizstu Nurcahyanto; Kaisar Bintang Putra (Universitas Darul Ulum, 2025)
Water pollution due to human activities causes high levels of household wastewater called greywater. To reduce the impact of water pollution from greywater, wastewater needs to be processed to be safer for the environment. By utilizing technology and independent energy sources from Photovoltaics, a system was created that can purify wastewater and can be controlled and monitored using the Internet of Things. The research entitled